Extended-range prediction of south atlantic convergence zone rainfall with calibrated cfsv2 reforecast - Hirata, F. E., Grimm , A. M. (My University, 2017)
During the 2010&ndash2011 wet season in Brazil, widespread landslides triggered by heavy rainfall killed hundreds of people and displaced nearly 35,000. The extreme precipitation was associated with the formation of the South Atlantic convergence zone (SACZ). Even though the physical mechanisms behind the formation and persistence of subtropical convergence zones are still unclear, we demonstrate that early predictions of heavy rainfall in the SACZ region are possible. Precipitation rate hindcasts from the NCEP Climate Forecast System version 2 are calibrated with the aid of a gridded precipitation dataset. When the calibration was applied to the 2010&ndash2011 events, the hindcasts were able to depict both active and break phases of the SACZ with up to 2 weeks in advance during a period of relatively weak intraseasonal variability associated with the Madden&ndashJulian Oscillation (MJO).
Keywords: rainfall, South Atlantic convergence zone